Effects of elevated CO2 on biomass and fungi associated with two ecotypes of ragweed (Ambrosia artemisiifolia L.) - Runion, G. Brett; Prior, Stephen A.; Price, Andrew J.; McElroy, J. Scott; Torbert, H. Allen (Frontiers in Plant Science, 2014)
Herbicide resistant weed populations have developed due to the repeated application of herbicides. Elevated concentrations of atmospheric CO2 can have positive effects on weed growth, but how rising CO2 might affect herbicide resistant weeds is not known. Ragweed (Ambrosia artemisiifolia L.) ecotypes known to be resistant or susceptible to glyphosate herbicide were exposed to either ambient or elevated (ambient + 200 µmol mol-1) concentrations of CO2 in open top chambers. Plants were harvested following 8 weeks of CO2 exposure; at this time, they had begun to exhibit disease symptoms including spots on leaves and stems. Elevated CO2 significantly increased top, root, and total plant biomass. Also, glyphosate resistant plants had significantly greater top, root, and total biomass than plants susceptible to the herbicide. There were no significant CO2 by ecotype interactions. Fungi from 13 genera were associated with ragweed, several of the which can be either pathogens (i.e., Alternaria, Fusarium, Rhizoctonia), aiding the decline in health of the ragweed plants, or saprophytes existing on dead plant tissues. The common foliar disease powdery mildew was significantly higher on susceptible compared with resistant ragweed. Susceptible plants also showed an increased frequency of Rhizoctonia on leaves and Alternaria on stems; however, Fusarium occurred more frequently on resistant ragweed leaves. Fungi were not affected by CO2 concentration or its interaction with ecotype. This study reports the first information on the effects of elevated CO2 on growth of herbicide resistant weeds. This is also the first study examining the impact of herbicide resistance and elevated CO2 on fungi associated with weeds. What effects herbicide resistance might have on plant diseases and how rising atmospheric CO2 might impact these effects needs to be addressed, not only with important weeds but also with crops.